2004
DOI: 10.1210/jc.2003-031804
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and Breast Cancer Risk

Abstract: Adiponectin, an adipocyte-secreted hormone, is closely and inversely associated with insulin resistance and was recently found to be inversely and independently associated with endometrial cancer. Because insulin resistance in the setting of obesity has also been associated with the development of breast cancer, we have hypothesized that decreased adiponectin levels might underlie the association between breast cancer and obesity/insulin resistance. We evaluated the association of adiponectin with the occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
377
5
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 482 publications
(400 citation statements)
references
References 35 publications
12
377
5
6
Order By: Relevance
“…IGFBP-1 was directly related with ovarian (Dal Maso et al, 2004a) and, possibly, endometrial cancer (Augustin et al, 2004), whereas an inverse association emerged with colorectal cancer (Kaaks et al, 2000). An inverse association with endometrial (Petridou et al, 2003;Dal Maso et al, 2004b) and breast cancer (Mantzoros et al, 2004) risk emerged for plasma adiponectin.…”
Section: Introductionmentioning
confidence: 89%
“…IGFBP-1 was directly related with ovarian (Dal Maso et al, 2004a) and, possibly, endometrial cancer (Augustin et al, 2004), whereas an inverse association emerged with colorectal cancer (Kaaks et al, 2000). An inverse association with endometrial (Petridou et al, 2003;Dal Maso et al, 2004b) and breast cancer (Mantzoros et al, 2004) risk emerged for plasma adiponectin.…”
Section: Introductionmentioning
confidence: 89%
“…Blinded adiponectin measurements were performed by a radioimmunoassay procedure with a sensitivity of 2 ng ml À1 , and intra-assay coefficient of variation of o10% as previously described (Petridou et al, 2003;Dal Maso et al, 2004;Mantzoros et al, 2004b). Average preservation time was similar for cases and controls, and adiponectin levels do not systematically change with storage time.…”
Section: Methodsmentioning
confidence: 99%
“…This hormone has also been inversely associated with both adult forms of cancer that have been epidemiologically investigated, namely breast cancer (Miyoshi et al, 2003;Mantzoros et al, 2004b) and endometrial cancer (Petridou et al, 2003;Dal Maso et al, 2004). In a recent in vitro study Yokota et al have investigated the functions of adiponectin in haematopoiesis and found that adiponectin predominantly inhibits proliferation of myeloid cell lines, and induces apoptosis in myelomonocytic leukaemia lines, but did not suppress proliferation of erythroid or lymphoid cell lines.…”
mentioning
confidence: 99%
“…Acrp30 is found at high concentrations (2-20 mg ml À1 ) in human serum (Arita et al, 1999;Bondanelli et al, 2001;Miyoshi et al, 2003;Mantzoros et al, 2004;Chen et al, 2006;Korner et al, 2007;Takahata et al, 2007). There are several different forms of Acrp30 in plasma that bind with varying affinity to the two different Acrp30 receptors, AdipoR1, and AdipoR2 (Yamauchi et al, 2003a).…”
mentioning
confidence: 99%
“…With respect to breast cancer, lower serum Acrp30 levels have been reported for postmenopausal women with breast cancer (Bondanelli et al, 2001;Miyoshi et al, 2003;Mantzoros et al, 2004). In vitro assays have indicated that the addition of Acrp30 to the human MDA-MB-231 breast cancer cell line-induced growth arrest and promoted apoptosis (Kang et al, 2005;Wang et al, 2006).…”
mentioning
confidence: 99%